Intermediate accounting - Chasteen, Lanny G.; Flaherty, Richard E.; O'Connor, Melvin C. (New York : McGraw-Hill, 1995)
Business
Keywords: Intermediate accounting; Financial accounting; Reporting; Financial investment; Income tax